Pengaruh Edukasi Vulva Hygiene Terhadap Lama Penyembuhan Luka Perineum Pada Ibu Nifas - Enny; Widiya , Novalia; Susanti; Sarkiah (Jurnal Ilmiah JKA (Jurnal Kesehatan Aeromedika), 2024)
During the birth process, a mother will experience internal injuries in the birth canal. Vulvar hygiene during the postpartum period must be carried out, because a lot of blood and dirt comes out of the vagina. The vagina is an area close to where you urinate and defecate and is an open organ, making it easier for germs in this area to spread to the uterus, causing infection to occur. The objective of the research was To determine the effect of Vulva Hygiene education on the healing time of perineal wounds in postpartum mothers at Balangan Regional Hospital. This research used a Quasy Experimental Design, Non-Equivalent Control Group. The sampling technique used was purposive sampling with 15 intervention groups and 15 control groups. The research was conducted on 15-22 January 2024 at Balangan Regional Hospital. The instruments used are checklist sheets and observation sheets. Data were analyzed using SPSS. The results showed that mothers who received vulva hygiene education had a fast wound healing process of ≤ 6 days, while mothers who did not receive vulva hygiene education had a slow wound healing process of > 6 days. Based on the chi square test, the results show that the p value is 0.010 or <0.05, which means H0 is rejected and Ha is accepted. There is a relationship between vulva hygiene education and the length of healing of perineal wounds at Balangan Regional Hospital.